Emergência da leitura de palavras de inglês com recombinação de onset e rime em braille e alfabeto romano em relevo para cegos - AGUILAR, Fábio (Universidade Federal do Pará, 2018)
Based on the equivalence paradigm, research on recombinative reading has evidenced that pardal syllabic control makes reading emergency difficult, and the need for control for all the word syllables in order to promote generalized reading. Recent research has shown the explicit teaching of discrimination of teaching syllables promotes recombinative reading and new recombined syllables. It also promptly promotes text reading with understanding of words formed by these syllables. In these studies, partia.' control is not established and recombinative reading emergency is promptly promoted. Teaching of new words through recombination of words by onset and rime segmentation has been showed as a facilitator element when the English language is taught as a mother tongue. By using the Braille system and Roman alphabet in raised letters to the blind people, it was investigated if using word discrimination with onset/rime segmentation it will facilitate the reading of new words in English as a second language. Three persons with visual impairment and fluent in Braille participated in the study. The study was divided in three parts. On Phase I a pre-test was given, conditional discrimination teaching of single words and the text reading test of teaching and recombined single words under two conditions, in Braille and in Roman alphabet in raised letters. On Phase II a test of word tpyt reading was applied, teci and teaching of AB relations (dictated words — objects), AC relation test (dictated word —printed words), BC (objects printed words) and CB (printed words objects) with single and composite words and a dictated test and copy. Phase III was identical to Phase II, replacing the single words by composite words. The emergence of new reading simple words and typeset in a combined English and printed in Braille on the Roman alphabet in relief occurred promptly in blind subjects. In testing the relationships emerging and copy test and dictation readily achieved all the criteria of success. The results confirm the efficiency of the procedure used in the emergence of rcading Singlc wutt15, wmpuunds and recombined in tnglish atter teaching conditional discrimination segmentation using onset / rime in the blind. The stimulus equivalence procedures to promote the emergence of reading with comprehension of words composed in combined and recombined in blind people. These results indicate that the procedure was effective teaching-learning can be characterized as errorless-learning. The results show the need to generate new teaching procedures more economical and efficient like alternative to the inclusion occuring.